(untitled) (Scientific journal of the Fergana State University, 2024)
The chemical composition of the essential oil extracted from the aerial parts of Haplophyllum acutifolium (DC.) G. Don, growing in the Bo‘stonliq district of Tashkent region, was studied using hydrodistillation. Gas chromatography-mass spectrometry (GC-MS) analysis revealed the presence of 74 components, which constitute 94.5% of the essential oil mass. It was found that the essential oil contains a high proportion of sesquiterpene hydrocarbons (51.2%) and oxidized sesquiterpenes (19.0%). The main components of the essential oil include α-elemol (12.6%), germacrene B (12.5%), β-caryophyllene (8.4%), 3-methyl-2-butenal (4.9%), germacrene D (4.5%), δ-cadinene (3.1%), δ-selinene (3.0%), and spatulenol (2.4%).